Design and analysis of tubular slotted linear generators for direct drivewave energy conversion systems - Mohd Zamri, N.A. (MDPI AG, 2020)
Linear generator utilization in a wave energy converter (WEC) is an attractive alternative to a rotary generator. This paper presents the design of a permanent magnet linear machine (PMLM) for WEC applications in low wave power areas. In this paper, the wave height and vertical speed of Malaysian water is used for the simulation and design. Two design variants are introduced which are tubular PMLM with no spacer (TPMLM-NS) and tubular PMLM with spacer (TPMLM-S). Finite element analysis (FEA) has been conducted to investigate the performance and to refine the main dimensions of the design in terms of split ratio, pitch ratio and tooth width. The FEA results are then validated using an analytical method which is established according to the design's magnetic field distribution. Based on main dimension refinement, it can be deduced that both the split ratio and the pitch ratio have a significant influence on the airgap flux density and back EMF of the design. The obtained FEA results also reveal that the TPMLM-NS variant is capable of producing 240 V back EMF, 1 kW output power with satisfactory efficiency. Consequently, this indicates the capability of the design to convert wave energy with good performance. Additionally, good agreement between the analytical predictions and FEA results was obtained with a low percentage of error, thus providing concrete assurance of the accuracy of the design. Â© 2020 by the authors.